Reid colposcopic index evaluation: Comparison of general and oncologic gynecologists - Apiwat Aue-Aungkul (2018)
The Reid colposcopic index (RCI) helps physicians for interpret the results of colposcopic examination. To compare the accuracy of RCI in colposcopic evaluation between general and oncologic gynecologists, this prospective trial was conducted by invited women over 20 years of age who were scheduled for a colposcopy at Chiang Mai University Hospital between August, 2008 and May, 2014 to participate. Pregnant patients or those having a history of hysterectomy or conization were excluded. During the colposcopy, all patients were simultaneously evaluated by general and oncologic gynecologists utilizing the RCI. Further management with either a biopsy or LEEP in each patient was dependent on the decision of the attending oncologic gynecologist. The accuracy of the RCI in diagnosing HSIL or more was calculated by the comparison with the final histology. Finally, 135 patients were recruited into this study. The sensitivity, specificity, PPV, NPV, and accuracy of RCI in diagnosing HSIL or more in general gynecologists were 45.2%, 80.7%, 41.1%, 83.2% and 72.6% while in the oncologic gynecologists were 51.6%, 85.6%, 51.6%, 85.6% and 77.8%, respectively. The difference in accuracy between evaluator groups was not significant (p-value=0.28). Of 3 patients with invasive cervical cancer, all were undetected by the general gynecologists using RCI while only 1 invasive cervical cancer was missed via RCI by the oncologic gynecologists. We conclude that RCI could be used by general gynecologists in provincial hospitals with major concerns about missing invasive cervical cancer. A short training period regarding colposcopy might help to resolve this problem.